2011
DOI: 10.1186/1743-422x-8-248
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatitis C Virus 3a genotype entry through Glanthus Nivalis Agglutinin

Abstract: BackgroundHepatitis C Virus (HCV) has two envelop proteins E1 and E2 which is highly glycosylated and play an important role in cell entry. Inhibition of virus at entry step is an important target to find antiviral drugs against HCV. Glanthus Nivalis Agglutinin (GNA) is a mannose binding lectin which has tendency for specific recognition and reversible binding to the sugar moieties of a wide variety of glycoproteins of enveloped viruses.ResultsIn the present study, HCV pseudoparticles (HCVpp) for genotype 3a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…[ 32 ] Molecular docking of GNA and HCV glycoproteins (E1 and E2) has indicated that GNA inhibits HCV entry into cells by binding N-linked glycans. [ 33 ] Taken together, these data indicate that some glycans of HCV envelope glycoproteins play a major role in the entry of HCV in cells. Thus, lectins are an attractive target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 85%
“…[ 32 ] Molecular docking of GNA and HCV glycoproteins (E1 and E2) has indicated that GNA inhibits HCV entry into cells by binding N-linked glycans. [ 33 ] Taken together, these data indicate that some glycans of HCV envelope glycoproteins play a major role in the entry of HCV in cells. Thus, lectins are an attractive target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, cyanovirin-N can inhibit HCV infection by binding the N-linked glycans on its surface, preventing the interaction between E2 and the entry receptor CD81 [ 53 ]. Other studies demonstrated that CV-N, Microcystis viridis lectin (MVL), and Galanthus nivalis agglutinin (GNA) inhibit HCV in vitro , with IC50 values of 0.6 nM, 30.4 nM, and 11.1 nM, respectively, likely through distinct and complex modes of action [ 55 , 75 ].…”
Section: Lectins Are Active Against Viruses Other Than Hivmentioning
confidence: 99%
“…The GNA lectin has exclusive binding specificity for mannose and has been characterized in particular for its potent inhibition of retroviruses (Akkouh et al, 2015). GNA inhibits hepatitis C virus infection of serum in a dose-dependent manner by binding N-linked glycans located at the top of the viral envelope (Ashfaq et al, 2011). Additionally, GNA selectively inhibits several varieties of immunodeficiency type 1 and 2 viruses in different cell types (Balzarini et al, 2004) and prevents cell-cell fusion in cells expressing HIV viral envelope glycoproteins and T cells (CD4 + ) (Yee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%